SYSTEMIC ARTERIAL HYPERTENSION IN EARLY HEALTH: PECULIARITIES IN PREVENTION AND TREATMENT IN PRIMARY CARE - de Sousa Assis, Sonária; Caroline de Sousa, Anne; de Lira Silva, Macerlane; Barros de Quental , Ocilma (Health and Society, 2022)
This study aimed to identify the factors that make it difficult for the elderly population to adhere to the prevention and treatment of blood pressure, as well as to highlight the contribution of primary care to solving this problem. For the investigation to be carried out, a narrative review of the literature was chosen, where searches were carried out in the scientific databases: LILACS, BDENF, SCIELO and MEDLINE. Through a detailed analysis of the searches and applicability of the defined eligibility criteria, 10 articles were selected to compose the final sample. The results evidenced through scientific evidence indicate that the elderly in situations of economic vulnerability or in situations of abandonment have greater difficulty both in the diagnosis and in following the pharmacological treatment with antihypertensive drugs. Allied to this, the lack of information regarding health education is one of the biggest challenges faced by the multidisciplinary team that works in the basic health unit. Thus, health promotion strategies should be painted in actions aimed at the community, especially for the elderly and their caregivers, on the importance of actively seeking health services, as well as the importance of following blood pressure treatment for the prevention of diseases. grievances. In this bias, it is of fundamental importance that health professionals are prepared to carry out health education, and to meet the needs and demands of each individual according to their needs and clinical particularities.